PENGAPLIKASIAN MODEL KOMUNIKASI OSGOOD AND SCHRAMM OLEH PENGAJAR TK DALAM ACARA PARENTS WORKSHOP DI HIGHSCOPE BINTARO - Menati Fajar Rizki (Communicology: Jurnal Ilmu Komunikasi, 2018)
ABSTRACT The teacher is a person who is very close to students at school. The teacher teaches a variety of things, from basic lessons to ways of communicating and good attitudes to socializing to his students. In the process of forming kindergarten growth and development, it takes a balance between teaching at school and at home. In this case the role of parents immediately becomes a major factor in the success of teachers and parents in educating children. One way is to equate how to teach at school with at home. Various kinds of activities and rules that are carried out at school should also be done at home. To achieve this, a parents workshop was held at the highscope bintaro school by applying the Osgood Schramm communication model in it. This is related to the inappropriate communication methods of the instructors, so that they often experience different perceptions with parents. Based on the Osgood & Schramm communication model, it is expected that teachers can convey information that is appropriate to the needs of parents, resulting in the same perception in how to educate children with special needs. The method used is a qualitative descriptive analysis method with in-depth interviews with parents who have children with special needs at the Highscope Indonesia Bintaro School. Interviews were conducted with purposive sampling technique. The results of the research found were new parents knowing how to deal with children with special needs by interpreting information from the teacher in the workshop. In addition, there was a message exchange between parents and their students at home with their teachers in their active learning methods. The parents workshop program can be a good forum and is very useful in equating the perceptions of parents and teachers aimed at educating children to be more independent. Keywords: Teachers, Parents of Students, Parents Workshop, Osgood Schramm Communication Model, perception ABSTRAK Guru merupakan orang yang sangat dekat dengan murid di sekolah. Guru mengajarkan berbagai macam hal, mulai dari pelajaran-pelajaran dasar hingga cara berkomunikasi dan sikap yang baik untuk bersosialisasi kepada para muridnya. Dalam proses pembentukan tumbuh kembang anak TK, dibutuhkan keseimbangan antara pengajaran di sekolah dengan di rumah. Dalam hal ini peran orang tua serta merta menjadi faktor utama berhasilnya guru dan orang tua dalam mendidik anak. Salah satu caranya adalah dengan menyamakan cara mengajar di sekolah dengan di rumah. Berbagai macam kegiatan serta aturan-aturan yang dilakukan di sekolah hendaknya dilakukan pula di rumah. Untuk mencapai itu semua diadakanlah kegiatan parents workshop di sekolah highscope bintaro dengan mengaplikasikan model komunikasi Osgood Schramm di dalamnya. Hal ini berkaitan dengan cara berkomunikasi yang kurang tepat dari para pengajar, sehingga sering mengalami perbedaan persepsi dengan orang tua. Dengan berdasar pada model komunikasi Osgood & Schramm, diharapkan para guru dapat menyampaikan informasi yang sesuai dengan kebutuhan orang tua, sehingga menghasilkan persepsi yang sama dalam cara mendidik anak berkebutuhan khusus. Metode yang digunakan adalah metode analisis deskriptif kualitatif dengan wawancara mendalam kepada orang tua yang memiliki anak berkebutuhan khusus di Sekolah Highscope Indonesia Bintaro. Wawancara dilakukan dengan tehnik purposive sampling sebagai salah satu tehnik pengumpulan data. Hasil penelitian yang ditemukan adalah orang tua baru mengetahui bagaimana cara menangani anak berkebutuhan khusus dengan menafsirkan informasi dari guru dalam acara workshop tersebut. Selain itu terjadi pertukaran pesan antara orang tua dengan cara didiknya di rumah dengan guru dengan cara didik active learningnya. Acara parents workshop dapat menjadi wadah yang baik dan sangat berguna dalam penyamaan persepsi orang tua dan guru yang bertujuan untuk mendidik anak menjadi lebih mandiri. Kata Kunci: Guru, Orang Tua Murid, Parents Workshop, Model Komunikasi Osgood Schramm, persepsi